Analisis Sosiologi Sastra dalam Puisi Mata Luka Sengkon Karta Karya Peri Sandi - Seftia Wulan Ayu Ningrum; Akhmad Fatoni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The poem Mata Luka Sengkon Karta Peri Sandi has a strong sociological element. This poem focuses on the problem of legal injustice and other social realities. This is done through a sociological literary approach. The people depicted in this poem, Sengkon and Karta, are representations of people who are victims of errors in the Indonesian legal system. This poem uses expressive and symbolic language to describe the helplessness, suffering, and hopes of the oppressed. This study aims to determine how the social and political context influences the creation of the poem, as well as how the poem functions as a social critique of the state of law in Indonesia. This study finds that Mata Luka Sengkon Karta is not only an aesthetic work; it also functions as a tool to convey the voices of marginalized communities, using the theory of sociology of literature.